St. Lucian Kwéyòl on St. Croix: How gender and education affect language choice and attitudes in a multilingual context - Mitchell, Edward; Ursulin Mopsus, Diana (Arborescences)

(untitled) (Département d'études françaises, Université de Toronto, 2011)
Based on interviews conducted within a community of St. Lucian Creole (Kwéyòl) speakers on the island of St. Croix, U.S. Virgin Islands, the authors investigated the use of and attitudes towards Kwéyòl, English, Spanish, and Crucian Creole, the four most widely-spoken languages on St. Croix. The article examines the roles of two social variables, namely gender and education, in questions of language choice and attitudes in this bilingual creolophone community. Some of the more remarkable revelations of this study were found in the many apparently conflicting responses. On the one hand, we observed a general trend towards the loss of Kwéyòl, yet on the other, pride in the language is exceedingly high. We observed a strong tendency pointing towards a taboo against speaking Kwéyòl in public on St. Croix, while at the same time, a significant number proclaimed the right to speak Kwéyòl in public.